1995
DOI: 10.1029/94jb02944
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic fault slip associated with the 1992 Mw 6.1 Joshua Tree, California, earthquake: Implications for the Joshua Tree‐Landers earthquake sequence

Abstract: Coseismic surface deformation associated with the Mw 6.1, April 23, 1992, Joshua Tree earthquake is well represented by estimates of geodetic monument displacements at 20 locations independently derived from Global Positioning System and trilateration measurements. The rms signal to noise ratio for these inferred displacements is 1.8 with near-fault displacement estimates exceeding 40 mm. In order to determine the long-wavelength distribution of slip over the plane of rupture, a Tikhonov regularization operato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…It is found that the spatial distribution of aftershocks is well explained in terms of a Coulomb failure criterion [ King et al , 1994] that involves a linear combination of the shear and normal tractions from a primary earthquake evaluated on a secondary fault plane. (Counterexamples, though relatively few, may be noted [ Astiz et al , 2000; Bennett et al , 1995; Dodge et al , 1995; Du and Aydin , 1993]. ) The time dependence of aftershock occurrence is less well understood, with chief candidate processes being rate‐ and state‐dependent friction [ Gross and Kisslinger , 1997; Gross and Bürgmann , 1998; Price and Bürgmann , 2002], dissipation of pore fluid gradients [ Jaume and Sykes , 1992], and viscoelastic relaxation of the lower crust and mantle [ Deng et al , 1999].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the spatial distribution of aftershocks is well explained in terms of a Coulomb failure criterion [ King et al , 1994] that involves a linear combination of the shear and normal tractions from a primary earthquake evaluated on a secondary fault plane. (Counterexamples, though relatively few, may be noted [ Astiz et al , 2000; Bennett et al , 1995; Dodge et al , 1995; Du and Aydin , 1993]. ) The time dependence of aftershock occurrence is less well understood, with chief candidate processes being rate‐ and state‐dependent friction [ Gross and Kisslinger , 1997; Gross and Bürgmann , 1998; Price and Bürgmann , 2002], dissipation of pore fluid gradients [ Jaume and Sykes , 1992], and viscoelastic relaxation of the lower crust and mantle [ Deng et al , 1999].…”
Section: Introductionmentioning
confidence: 99%
“…We calculate stresses from the same three earthquakes (the "main shock" group) and contrast these with those of the smaller but more numerous and clustered "aftershocks" (the "aftershock" group). For the main shocks Joshua Tree, Landers, and Big Bear, we calculate stresses from slip models published by Bennett [1995], Wald and Heaton [1994], and Jones and Hough [1995], respectively (available from http://equake-rc.info/srcmod/). For the smaller events for which no finite-fault models are available we use the focal mechanism catalog of Yang et al [2012] (in the following referred to as YHS catalog), which contains n = 6613 earthquakes with M ≥ 2 within 95 days of the M w 6.4 Big Bear earthquake (the last of the three large events) within the study region of Woessner et al [2011] (117.5…”
Section: Introductionmentioning
confidence: 99%
“…Using such small search volumes, the method does not find seismicity that elucidates the fault zone structure of the Joshua Tree fault. Alternatively, one could choose very large search volumes (see single search volume for the Joshua Tree segment or roughly 25 km) and one would arrive at planar models similar to those used in prior studies [e.g., Bennett et al , ]. We limit the size of the search volumes to 10 km along strike, or nearly the depth‐extent (12 km) of the seismogenic portions of the faults in the region.…”
Section: Methodsmentioning
confidence: 99%
“…There a further dense cloud of seismicity is found. The relative sparsity of the seismicity in the center of the Joshua Tree fault is attributed to main rupture location with a radius of roughly 5–6 km [ Bennett et al , ].…”
Section: Methodsmentioning
confidence: 99%